Therapy of lyme borreliosis - a review - Weber, K... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
There is some confusion regarding the recommended therapy of Lyme Borrelisosis. In the present paper current treatment standards are qutlined based on a review of the literature. Most patients with Lyme Borreliosis benefit from a single course with an effective antibiotic. However, in many but not all patients with recalcitrant Lyme Borreliosis, repeated courses with the same or other effective antibiotics may be necessary and prove to be beneficial.
Keywords: Adult; Child; Drug therapy; Lyme disease; Pregnancy